2010
DOI: 10.1111/j.1365-2516.2010.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the psychological burden of haemophilia

Abstract: Providing comprehensive care, counselling and support to haemophilic patients, and their parents have always been quite complex for haemophilia treatment centres. Nowadays, starting with recent developments in genetic counselling, prenatal diagnosis and carrier testing, the psychological burden on patients and parents might possibly have increased, compared with even the recent past. The emotional strains and worries associated with a possibly affected newborn and his care through childhood and adolescence may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…Therefore, a good therapeutic alliance with the patient must be accompanied by assessment and counselling in other aspects including satisfaction, perceived difficulties and barriers, and emotional needs. Raising awareness of this will result in the patient benefiting from the recent improvements in treatments .…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a good therapeutic alliance with the patient must be accompanied by assessment and counselling in other aspects including satisfaction, perceived difficulties and barriers, and emotional needs. Raising awareness of this will result in the patient benefiting from the recent improvements in treatments .…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
“…Haemophilia is a condition usually diagnosed during childhood, and psychosocial aspects of the early years have attracted much attention in the literature. Many authors , including our group , have addressed the psychological impact of the disease, and the necessary support for the family and young patient as he experiences growing up with haemophilia from infancy, through childhood and adolescence . However, the issues of adults or ageing persons with haemophilia (PWHs) have been less frequently discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A global survey found that overall compliance rates declined in an age-related manner, with the lowest rate at 36% in those aged 19–58 years 54. Other major barriers to adherence include patient failure to understand treatment benefits, patient denial, poor venous access, lack of family support, lifestyle interference, teenage rebellion, time constraints, relief or disappearance of symptoms, and forgetfulness 54,55…”
Section: Psychosocial Impact Of Inhibitors On Patients With Hemophiliamentioning
confidence: 99%
“…The psychological, societal, and economic burden of haemophilia has been documented for a number of European countries [1317]; few studies have taken a standardised methodology across multiple countries simultaneously [18], and sought to amalgamate all three levels of burden for severe disease. The overall aim of the CHESS study was to capture the annualised economic and psychosocial burden of severe haemophilia in the EU5.…”
Section: Introductionmentioning
confidence: 99%